Peran Usaha Mikro Kecil dan Menengah (UMKM) Terhadap Kesejahteraan Masyarakat di Kecamatan Betara Menurut Perspektif Ekonomi Syariah - Dara Anjelita; As'ad Isma; M. Maulana Hamzah (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The results of this research show the role of micro, small and medium enterprises (MSMEs) in the welfare of society in Betara sub-district. This research aims to look at the role of micro, small and medium enterprises so that they can increase the economic sustainability of families for the sake of community welfare. This research aims to find out the role of micro, small and medium enterprises in community sustainability in MSMEs in Betara sub-district. The results of this research show that the existence of MSMEs has a very important role in the welfare of the community by opening up employment opportunities and increasing the income of the surrounding community so that they can meet their daily needs such as food, as well as other needs such as housing, family health and the need for children's education. their children and create employment opportunities for the local community to help improve community welfare. In its implementation, it is still said to be ineffective, this is because there are still many shortcomings that occur in finding solutions to the problems faced by entrepreneurs, especially micro, small and medium enterprises, including capital, so that there is a lack of labor caused by a lack of capital for MSMEs which causes their business to suffer. experienced ups and downs, affecting production and income.